Nutritional Status of Child of Well-Nourished Mother Vs Malnourished Mother - Fatima Masood, Aymen Masood, Hafiz Umer Farooq, Muhammad Akhtar Masood, Sumera Ehsan, Hatf Rana (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The nutritional status of children is a good predictor of the community’s overall nutritional profile. The nutritional requirements of women before conception, during pregnancy, and during breastfeeding are referred to as maternal nutrition. Globally, 165 million children under the five years are malnourished. It accounts for at least half of all the childhood deaths worldwide. Objective: To find the nutritional status of child of well-nourished mother vs. malnourished mothers Methodology: This comparative1observational study was conducted at Pediatrics Department, Masood Hospital & The Children Complex, Rahim Yar Khan. The study included 294 mothers of children aged 6 to 59 months who were both well-nourished and malnourished. Both mothers of children who were well-nourished when they were admitted to the ward and mothers of children who were malnourished when they were admitted to the NSC were included. Mothers’ Body Mass Index (BMI) was assessed, and children’s MUAC was obtained. The information was gathered using a designed questionnaire that asked about the mother’s age, BMI, the children’s age and gender, MUAC.Data was entered in SPSS V 25. Result: Total 294 children were included. Among1them 158(53.7%) mothers malnourished children & 136(46.3%) mothers of well-nourished children. The mean age of children was 2.50 + 0.98. There were 129(43.9%) male children and 165(56.1%) female children. Out of malnourished children, there were 31(19.6%) mildly undеr-wеіght, 9(5.7%) moderately undеr wеіght & 3(1.9%) were severely underweight. Furthermore, 134 mothers1of well-nоurіshеd children, 55(40.4%) mildly1undеrwеіght, 40(30.9%) moderately1undеrwеіght & 27(19.9%) were severely1underweight. There were 145 mothers had normal Hb and 149 mother’s anemic. Practical Implication: The purpose of this research was to determine if there is a correlation between children malnutrition and the health of their mothers. The findings of this study may aid in bringing the attention of the entire family, and notably the mothers, to the treatment of children suffering from severe acute malnutrition. Children can be protected from developing malnutrition through early diagnosis and treatment. Conclusion: Findings of our study showed that many children having history of mother malnutrition were undernourished. Study concluded that malnutrition was not problem of only mothers; it was also a big problem for children as well as whole family. In addition to caring for the malnourished child who has been admitted, the underlying causes of malnutrition must be identified and addressed if the problem is to be resolved for the entire family. Keywords: Body Mass Index, Nutritional Assessment, Malnutrition, Well-nourished